Finger Counting and (2D:4D) Digit Ratio in Spatial-Numerical Association. (January 2016) - Fabbri, Marco; Natale, Vincenzo
It is reported that a canonical and cultural finger counting habit influences the spatial-numerical association. The digit ratio (the ratio between the lengths of the index and ring fingers as a putative indicator of prenatal androgen exposure) also plays an effect on space-number representation, reflecting a stronger left-to-right number representation in people with a short index finger and longer ring finger (i.e., 2D:4D ratio). It is unknown whether the finger counting habit and digit ratio have an effect on spatial-numerical association independently from each other or whether they interact with each other. In Study 1, the digit ratio and finger counting mapping were recorded in right handers. The participants performed number-to-position, digit string bisection, and physical line bisection tasks. In the number-to-position task, a finger counting effect was found, as well as a significant interaction between factors. A digit ratio effect was observed in the digit string bisection task. In Study 2, digit ratio and finger counting mapping were recorded in right and left handers. The results showed that the finger counting habit influenced the spatial biases in both numerical tasks. A significant interaction between finger counting and digit ratio was found in both numerical tasks when only the left hand was considered. The results are discussed considering the embodied nature of the spatial-numerical association.